Fraud Hexagon sebagai Determinan Fraudulent Financial Statement dengan Proksi Beneish M-Score pada Perusahaan Properti dan Real Estate - Erissa Dwi Yunita Sary; Sri Luna Murdianingrum (Politeknik Ganesha Medan, 2026)
This research aims to examine the determinants of fraudulent financial statements by analyzing the elements of Fraud Hexagon Theory through the Beneish M-Score approach in property and real estate companies listed on the Indonesia Stock Exchange (IDX) during the period 2021–2024. This research employs a quantitative approach using a purposive sampling method, resulting in 170 data observations. The data were analyzed using binary logistic regression with the assistance of SPSS version 25 to determine the probability of Fraud Hexagon Theory having a significant effect on fraudulent financial statements. The results indicate that financial stability and change of director have a significant positive effect on fraudulent financial statements, while nature of industry, change of auditor, CEO duality, and political connection do not have a significant effect. These findings suggest that financial pressure and changes in leadership structure are dominant factors in the occurrence of fraudulent financial statements in the property and real estate sector during the study period